Factores de riesgo asociados a cesárea iterativas vs. Parto vaginal en gestantes atendidas en el área de gineco-obstetricia del Hospital General IESS Babahoyo, octubre 2024- mayo 2025. - Bejarano Navarrete, Joyce Mileydi (2025)
Iterative cesarean section, also known as repeat cesarean section, versus vaginal delivery is a crucial topic when pregnancy is nearing its end. This is because a fine line separates these two procedures in terms of assessing the risks that can affect both the mother and the fetus. Therefore, it is essential to understand and analyze the risk factors. Objective: To identify the medical, obstetric, and psychosocial risk factors associated with the choice between iterative cesarean section and vaginal delivery in women with a history of previous cesarean section at the IESS General Hospital in Babahoyo. Method: The research was descriptive, cross-sectional, and retrospective, based on events that occurred at a specific time in the past. Population: This curriculum project included 1761 pregnant women who were treated at the IESS Babahoyo General Hospital between October 2024 and January 2025 and had one or more risk factors. Sample: Based on the finite statistical formula, 315 pregnant women were obtained for the study of this project, of which were selected according to inclusion and exclusion criteria during the period October 2024-January 2025. Results: According to the study, the risk factors that were most frequently presented were multiparity in 74%, the number of pregnancies in 46% of 2 to 4 pregnancies, the number of cesarean sections in 45% of 2 to 3 cesarean sections, short intergenic period in a percentage of 42%, with personal pathological antecedents in 37%, such as preeclampsia in 43% as a maternal complication and fetal distress as a fetal complication in 56%. Conclusion: Among the iterative cesarean sections vs vaginal delivery within the hospital institution, cesarean sections presented a higher percentage compared to vaginal delivery, due to several risk factors.